Comparison of kV Orthogonal Radiographs and kV-Cone-Beam Computed Tomography Image-Guided Radiotherapy Methods With and Without Implanted Fiducials in Prostate Cancer - (:unkn) unknown (CUREUS INC, 2020)
Introduction The aim of this study is to investigate the performance of kilovoltage (kV) cone-beam computed tomography (CBCT)- based adjustments with respect to kV-orthogonal fiducial marker-based matching in a group of patients with prostate cancer. Methods Twenty prostate cancer patients were evaluated retrospectively: 10 with implanted fiducial markers and 10 without. Daily orthogonal kV imaging was recorded prior to radiation delivery. Images were evaluated in the left-right (LR), anterior-posterior (AP), and superior-inferior (SI) directions by matching either the implanted fiducials or going off bony anatomy, depending on the presence or absence of markers, respectively. Cone-beam computed tomography (CBCT) imaging was also subsequently acquired and images were aligned with the planning CT. The couch shifts were calculated and the patient's position was adjusted accordingly. Standard deviations and random errors were also computed. Pearson correlation and Bland-Altman analysis were performed to evaluate relationships between the datasets. Results A total of 240 images were evaluated. The Pearson correlation coefficient for shifts applied to patients with markers using kV and CBCT was 88.3%, 87.8%, and 94.5% for the LR, AP, and SI directions, respectively. For those without markers, the respective values for the LR, AP, and SI directions were: 39.3%, 22.4%, and 3.7%. A Bland-Altman analysis comparing kV and CBCT in patients with markers, revealed R-2 values of 0.152, 0.282, and 0.097 in the LR, AP, and SI directions, respectively. The R-2 values for patients without markers were 0.008, 0.01, and 0.057, in the LR, AP, and SI directions, respectively. Conclusions Our data suggest that CBCT can be a viable option for image-guidance in clinical settings where fiducial markers are unavailable such as situations of inaccessibility or medical contraindications.
Keywords: prostate cancer; fiducial; imrt; igrt; kv-cbct